2021
DOI: 10.3390/ijerph18157915
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Public-Interest Short Message Service (SMS) in China during the COVID-19 Pandemic: Mobile User Survey and Content Analysis

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) has greatly threatened the global health system and triggered the public health emergency. In order to manage the COVID-19 pandemic, healthcare and prevention information have been delivered through omni-media channels (e.g., television, radio, social platform, etc.). As a traditional outlet, the short message service (SMS) can timely provide abundant anti-epidemic alerts to mobile users. In this paper, we aim to investigate mobile users’ attitudes toward COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Similarly, the short message service (SMS) can timely provide abundant anti-epidemic alerts to mobile users. SMS tracking platforms could be useful as an early warning system to refer patients with worsening clinical status to hospital-based care or additional clinician advice [ 77 ]. Yu et al’s study showed a positive attitude towards content and the necessity of public-interest in SMS during the pandemic [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the short message service (SMS) can timely provide abundant anti-epidemic alerts to mobile users. SMS tracking platforms could be useful as an early warning system to refer patients with worsening clinical status to hospital-based care or additional clinician advice [ 77 ]. Yu et al’s study showed a positive attitude towards content and the necessity of public-interest in SMS during the pandemic [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the more distant future, the TI Messenger will probably also offer function for communicating with patients. In other countries, such as China, SMS already was tested during the COVID-19 pandemic as an information channel on health-related topics for the population [30]. This option could also be implemented in Germany via TI messaging but would require further research and place additional demands on the media skills of all involved.…”
Section: Further Implicationsmentioning
confidence: 99%
“…It is the most commonly used service for data exchange in the world today. It has been determined that a number of 8.3 trillion SMSs have been sent overall and approximately 690 billion SMSs have been sent monthly across the world in recent years 1 .…”
Section: Introductionmentioning
confidence: 99%